2011
DOI: 10.1001/archgenpsychiatry.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Brain Regional α-[11C]Methyl-L-Tryptophan Trapping in Medication-Free Patients With Obsessive-Compulsive Disorder

Abstract: The results support previous reports of greater striatal and temporal lobe activity in patients with OCD than in healthy controls and suggest that these disturbances include a serotonergic component. Previously reported glucose metabolic disturbances in OCD involving the orbitofrontal and cingulate cortices, in comparison, might reflect postsynaptic changes in the serotonergic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 121 publications
2
14
0
Order By: Relevance
“…Regarding the ventral striatum, PET studies of patients with OCD at rest have shown increased activity of the caudate nuclei 47 that tended to decrease and J Psychiatry Neurosci 2012;37(4) normalize after successful treatment. 48,49 Similar findings showing the disturbed activity of the ventral caudate, which was found to predict OCD symptom severity, was also reported in studies using different methodologies (e.g., α-[(11)C]methyl-L-tryptophan brain trapping, 50 serotonin receptor binding, 51 magnetic resonance spectroscopy and volumetry 18,52 and preoperative electrophysiological unit recording 53 ). The fact that deep brain stimulation of the nucleus accumbens was found to be effective for managing treatment-refractory OCD also supports a major role of the ventral striatum in the pathophysiology of this latter condition.…”
Section: Discussionsupporting
confidence: 77%
“…Regarding the ventral striatum, PET studies of patients with OCD at rest have shown increased activity of the caudate nuclei 47 that tended to decrease and J Psychiatry Neurosci 2012;37(4) normalize after successful treatment. 48,49 Similar findings showing the disturbed activity of the ventral caudate, which was found to predict OCD symptom severity, was also reported in studies using different methodologies (e.g., α-[(11)C]methyl-L-tryptophan brain trapping, 50 serotonin receptor binding, 51 magnetic resonance spectroscopy and volumetry 18,52 and preoperative electrophysiological unit recording 53 ). The fact that deep brain stimulation of the nucleus accumbens was found to be effective for managing treatment-refractory OCD also supports a major role of the ventral striatum in the pathophysiology of this latter condition.…”
Section: Discussionsupporting
confidence: 77%
“…α-[ 11 C]MTrp has been used to study 5-HT synthesis capacity, and more generally, 5-HT metabolism, in various patient populations 22 24 . In particular, we previously used α-[ 11 C]MTrp to study baseline 5-HT synthesis capacity rates in OCD patients, and reported abnormally elevated α-[ 11 C]MTrp trapping, relative to controls, in temporal, striatal, and limbic regions 25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, all of the aforementioned studies only provide indirect evidence of a relationship between serotonergic systems and BDD, and do not prove serotonergic abnormalities underlie BDD pathophysiology. An investigation of serotonergic abnormalities using PET, similar to what has already been performed in individuals with OCD (Berney et al 2011; Perani et al 2008) could provide more definitive evidence of the role of serotonin in BDD.…”
Section: Neurochemistrymentioning
confidence: 91%